Impact of performance status on treatment outcomes: A real‐world study of advanced urothelial cancer treated with immune checkpoint inhibitors. Issue 6 (12th December 2019) - Khaki, Ali Raza; Li, Ang; Diamantopoulos, Leonidas N.; Bilen, Mehmet A.; Santos, Victor; Esther, John; Morales‐Barrera, Rafael; Devitt, Michael; Nelson, Ariel; Hoimes, Christopher J.; Shreck, Evan; Assi, Hussein; et al.
Abstract : Background: Immune checkpoint inhibitors (ICIs) represent an appealing treatment for patients with advanced urothelial cancer (aUC) and a poor performance status (PS). However, the benefit of ICIs for patients with a poor PS remains unknown. It was hypothesized that a poor Eastern Cooperative Oncology Group (ECOG) PS (≥2 vs 0‐1) would correlate with shorter overall survival (OS) in patients receiving ICIs. Methods: In this retrospective cohort study, clinicopathologic, treatment, and outcome data were collected for patients with aUC who were treated with ICIs at 18 institutions (2013‐2019). The overall response rate (ORR) and OS were compared for patients with an ECOG PS of 0 to 1 and patients with an ECOG PS ≥ 2 at ICI initiation. The association between a new ICI in the last 30 and 90 days of life (DOL) and death location was also tested. Results: Of the 519 patients treated with ICIs, 395 and 384 were included in OS and ORR analyses, respectively, with 26% and 24% having a PS ≥ 2. OS was higher in those with a PS of 0 to 1 than those with a PS ≥ 2 who were treated in the first line (median, 15.2 vs 7.2 months; hazard ratio [HR], 0.62; P  = .01) but not in subsequent lines (median, 9.8 vs 8.2 months; HR, 0.78; P  = .27). ORRs were similar for patients with a PS of 0 to 1 and patients with a PS ≥ 2 in both lines. Of the 288 patients who died, 10% and 32% started ICIs in the last 30 and 90 DOL, respectively. ICI initiation in the last 30 DOL was associated with increased odds of death in a hospital (odds ratio, 2.89; P  = .04). Conclusions: Despite comparable ORRs, ICIs may not overcome the negative prognostic role of a poor PS, particularly in the first‐line setting, and the initiation of ICIs in the last 30 DOL was associated with hospital death location. Abstract : This multi‐institution, retrospective cohort study shows that patients with an Eastern Cooperative Oncology Group performance status ≥2 (versus a performance status of 0‐1) have a comparable overall response rate but worse overall survival with treatment with an immune checkpoint inhibitor as first‐line therapy, whereas treatment initiation in the last 30 days of life is associated with increased odds of hospital death.